Arterial compliance is improved via enteral serine protease inhibition in experimental trauma/hemorrhagic shock - Joyce B. Li; Fernando dos Santos; Cynthia R. Muller; Nathalia J. D. Moreira; Luciano F. Borges; Maria Claudia C. Irigoyen; Geert W. Schmid-Schönbein; Erik B. Kistler; Erik B. Kistler (Frontiers in Physiology)
BackgroundSystemic hypotension remains a challenge in trauma/hemorrhagic shock (T/HS). Despite intensive vasopressor and fluid therapy, mean arterial blood pressure (MAP) may become refractory to treatment. Arterial compliance (AC) is a critical determinant of arterial hemodynamics but is often overlooked in acute shock states. Considering previous findings on the benefits of enteral protease inhibition in preserving vascular resistance after T/HS, this study investigated both the role of AC and the effects of enteral protease inhibition on AC in T/HS.MethodsWistar rats underwent experimental T/HS by laparotomy and exsanguination to induce a MAP of ∼40 mmHg for 90 min. Animals were randomized into three groups corresponding to the intervention: shed whole blood (WB), Lactated Ringer’s (LR), and LR with enteral gabexate mesilate treatment (LR+GM). Resuscitation (120-min period) was initiated by fluid reperfusion with a goal MAP of 65 mmHg. AC was measured via pulse wave velocity (PWV), passive pressure myography, and atomic force microscopy (AFM), with healthy donor arteries for comparison.ResultsPWV increased by ∼15% in all groups after shock. After resuscitation, LR-only animals maintained high PWVs, but significantly lower diastolic pressures (27 mmHg) compared to GM-treated (37 mmHg; p < 0.05) and those reperfused with WB (52 mmHg; p < 0.01). T/HS arteries, particularly the untreated LR arteries, exhibited leftward shifts in circumferential tension-strain curves. LR arteries exhibited higher tangent moduli (5 N/m; p < 0.01) at low physiological stresses, which was corroborated by reduced opening angles, increased mechanical stiffness, alterations in the extracellular matrix, and increased MMP/elastase-like activity. LR+GM and WB arteries displayed elastic moduli and vascular structures more similar to those of healthy arteries.ConclusionExperimental T/HS results in impaired AC, which is partially attenuated by enteral GM administration. Vascular biomechanical impairment may underlie the unrestored MAP in fulminant shock. By targeting modulators of AC, with enteral serine protease inhibition as an adjunct intervention, hemodynamic stability and patient outcomes may be improved in T/HS.